Cameroon Economic Update, January 2014, Issue No. 7 - World Bank (Washington, DC, 2014)
The Cameroon economic updates aim at sharing knowledge and stimulating debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. The notes thereby offer another voice on economic issues in Cameroon, and an additional platform for engagement, learning, and exchange. The average observed economic growth rate from 2010 to 2013 is a mere four percent, one percentage point below the vision 2035 targets. Achieving the official objectives set for 2020 will require Cameroon to move to double digit annual growth rates over the 2014-2020 period, compared to the 4.8 to 5.4 percent projected by the World Bank. This report looks at the quality of basic education to ensure that the right investments are made in people to build human capital, a key ingredient for sustainable economic growth. Cameroon has achieved significant progress over the last decade in expanding access to basic education. The number of students completing primary school, the primary completion rate, rose from 53 percent in 2001 to about 80 percent in 2011. The improvements in access to education also mask significant differences in education performance across and within individual regions, as well as between gender and income groups. The economic update suggests improving data collection in order to better monitor education service provision, assess more systematically student learning, increase in budget allocation to education as a whole, reprioritize public spending to the zones d'education prioritaires (Education Priority Zones) (ZEPs), ensure transparency in budget allocation, and revisit the textbook policy to ensure durability and affordability.